Long-term effects of duodenal mucosal resurfacing and liraglutide on glycaemic control in patients with type 2 diabetes - Max Nieuwdorp; Annieke C G van Baar; Jacques J G H M Bergman; Celine B E Busch; Julia Rubingh (BMJ Nutrition, Prevention & Health)
Introduction Endoscopic duodenal mucosal resurfacing (DMR) induces mucosal regeneration through hydrothermal ablation. Studies have shown that DMR improves hyperglycaemia in patients with type 2 diabetes. The INSPIRE study (n=16) aimed to eliminate insulin by combining DMR with a glucagon-like peptide-1 receptor agonist (GLP-1RA). At 18 months, 53% of patients were off insulin with adequate glycaemic control. This retrospective analysis evaluates long-term effects of DMR and GLP-1RA.Research design and methods Fourteen patients gave consent for the prolonged follow-up and data on glycaemic control, medication and DMR satisfaction were obtained via general practitioners. Primary endpoint was the number of patients off insulin with glycaemic control (haemoglobin A1c (HbA1c) ≤58 mmol/mol (7.5%)) at 4 years post DMR. Secondary endpoints were changes in HbA1c, fasting plasma glucose (FPG), weight, body mass index (BMI), use of glucose-lowering medications, treatment satisfaction and willingness to undergo DMR retreatment.Results Nine out of 14 patients (64%) were off insulin at 4 years. Of these, five patients (36% of study population) were adequately controlled. HbA1c and FPG did not change significantly, whereas BMI decreased at 3 and 4 years. Among the responders at 12 months, there was 80% durability at 4 years. Patients rated the DMR procedure 9 out of 10 and 86% were willing to undergo DMR retreatment.Conclusions Despite a stable number of patients remaining off insulin, a decrease in patients with adequate glycaemic control was observed. This suggests a slightly fading long-term DMR effect on glycaemia. High patient satisfaction and willingness for DMR retreatment indicate a promising avenue for further research.